Electrical and Mechanical Properties of 0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3)TiO3 (BZT–BCT) Lead Free Ferroelectric Ceramics Reinforced with Nano-sized Al2O3. Issue 1 (2nd January 2016) - Adhikari, P.; Mazumder, Ranabrata; Sahoo, Ganesh K.
Abstract : Al2 O3 nano-oxides (0–2.0 vol%) added 0.5Ba(Zr0.2 Ti0.8 )O3 –0.5(Ba0.7 Ca0.3 )TiO3 (BZT- 0.5BCT) ceramics have been prepared by the conventional solid-state reaction method. The effects of Al2 O3 nano-oxides on the phase formation, densification, dielectric, piezoelectric and mechanical properties (flexural strength, hardness) of the BZT-0.5BCT ceramics have been studied systematically. The synthesized powder could be densified to 96% of relative density at a temperature of 1350°C. It was observed that the addition of Al2 O3 up to 1 vol % could maintain the permittivity (ϵr ) at 3600 with low tanδ value of about 0.02 and d33 of 350pC/N. BZT-0.5BCT/Al2 O3 ceramics possess good mechanical properties viz. flexural strength of 92 MPa compared to pure BZT-BCT (74 MPa) ceramics.